INSURGENCIES IN CHILDREN’S LITERATURE: LITERARY MEDIATION FOR A DECOLONIAL EDUCATION - Alves Júnior, Laércio Francisco de Souza; Soares, Ivanete Bernardino (Literatura em Debate, 2025)
Studies on coloniality and its implications in Latin America denote the need for investment in an educational approach in the opposite direction of the historical inaccuracies of an epistemology that has silenced insurgent practices and knowledge. Once we believe that changing in the ethical posture in society should also be implemented at the individual level and since birth, and that literature is a privileged form of expressing children's imagination. Literary education must be grounded in an anti-racist ethic, through the qualified mediation of works that focus on themes and characters historically marginalized. This paper argues in favor of decolonizing knowledge and perception systems via literary education from childhood. For this purpose, it is presented a literature review based on theoretical contributions from authors such as Quijano (2005), Author (2021), Soares, Gebara, and Martins (2023), Bellestrin (2013), Walsh (2009), Candido (2012), and others. To illustrate the theoretical reflection, it is proposed a reading mediation strategy of the book Procura-se Carolina, by Otávio Júnior and Isabela Santos. The selected work promotes a black female character, no longer relegated to secondary roles but a protagonist and knowledge producer – a subversive potential against colonial logic.